Cordial labeling for the sum and union of the second power of paths and stars - Hefnawy A.I.; Elsid E.A.; Euat Tallah S. (Utilitas Mathematica, 2018)
A graph is said to be cordial if it has 0-1 labeling that satisfies certain conditions. In this paper we present necessary and sufficient conditions for cordial labeling applied to the sum of the second power of the path, P2 n with the star K1,m. Moreover, a similar result is established for the union P2 n U K1,m. © 2018 Utilitas Mathematica Publishing Inc. All rights reserved.